Effect of different conditions on the combustion interactions of blended coals in O2/CO2 mixtures. Issue 3 (June 2019) - Ma, Lun; Wang, Tingxu; Liu, Jichang; Fang, Qingyan; Guo, Anlong; Zhang, Cheng; Chen, Gang
Abstract: The combination of oxy-fuel and blended-coal combustion may be one of these effective methods to both reduce CO2 emissions and improve energy utilization efficiency in coal-fired power stations. The aim of this study is to investigate oxy-fuel combustion interactions of blended coals under different conditions using a thermo-gravimetric analyzer. The results show that compared with those in an O2 /N2 mixture, the promotive and inhibitive effect and the comprehensive interactions are considerably weaker in an O2 /CO2 mixture. In the O2 /CO2 mixture, both increasing the O2 concentration and decreasing the particle size result in decreasing the promotive effect but increasing the inhibitive effect and the comprehensive interactions, which increase the non-additive combustion characteristics. Enhancement of the heating rate increases the promotive effect but decreases the inhibitive effect and the comprehensive interactions, which weaken the non-additive combustion characteristics. Of these factors, the effects of the oxygen concentration and heating rate on comprehensive interactions are greater than that of particle size. This study provides useful information for the design and optimization of thermo-chemical conversion systems of coal blends in the O2 /CO2 atmosphere. Highlights: Ignition promotion and burnout inhibition exist during blended coal combustion. Weaker promotion, inhibition and interaction are shown in O2 /CO2 than in O2 /N2 . Higher oxygen shows weaker promotion, stronger inhibition and interaction. Smaller particle size shows weaker promotion, stronger inhibition and interaction. Higher heating rate shows stronger promotion, weaker inhibition and interaction.